Aerosol Physical‐Optical Properties and PBLH Under Different Air Pollution Levels From Ground Lidar and Satellite Observations Over Shouxian Area, China. Issue 24 (27th December 2021) - Zhang, Yuan; Wei, Fan; Luo, Hao; Su, Yueyuan; Feng, Yan; Huang, Yong; Yang, Jun; Wu, Yonghua; Han, Yong
Abstract: The physical and optical properties of aerosols and the change of planetary boundary layer height (PBLH) are of great scientific significance for the study of atmospheric environment and air quality. This paper intends to present integrated observations of aerosol physical‐optical characteristics and PBLH properties under different air pollution levels in Shouxian (National Climatology Observatory (32°26' N, 116°47' E)), China. The combined measurements of ground‐based Lidar and Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) are analyzed from December 2016 to November 2017 in this study. Results show that the extinction coefficients decrease significantly with height below 2 km. The extinction coefficients below 1 km, the aerosol optical depth (AOD), and the PBLH increase with the aggravation of pollution. The daily average aerosol extinction coefficient near the surface is about 0.78 km −1, the AOD is 0.87 ± 0.33 m (mean ± std, the same below), and the PBLH is 827 ± 132 m in polluted conditions (PM2.5  > 115 μg m −3 ). With the increase in pollution and the decrease in PBLH, more aerosols are accumulated at a lower height. The daily average ratios of AOD below PBLH (AODPBLH ) to total AOD (AODtot ) are about 64% in polluted conditions. According to the CALIPSO‐observed aerosol vertical profile, aerosols are identified for about 20.54% of the vertical space below 6 km altitude under polluted conditions. The spherical fine particles with lower particulate depolarization ratio (PDR, 79% of the PDR is <0.2), lower color ratio (CR, 64% of the CR is <0.75), and stronger scattering ability are dominant in 0∼2 km. Key Points: With the increase in pollution and the decrease in planetary boundary layer height, more aerosols are accumulated at the lower height The aerosol extinction coefficients decrease significantly with height below 2 km, and aerosol scattering ability is strong in 0∼2 km The regular fine particles with lower particulate depolarization ratio (PDR) (79% of the PDR is <0.2), lower lower color ratio (CR) (64% of the CR is <0.75) are dominant in 0∼2 km